Beyond Cognitive Satisfaction: Unveiling the Role of Spiritual Happiness and Store Image in Halal Retail Loyalty - Fuad Hasyim; Ririn Tri Ratnasari; Budi Sukardi; Fuad Dhiya Ul Husaen; Ferdi Arifin (Institut Agama Islam Negeri Ponorogo, 2026)
This study examines the association between brand positioning and service quality and halal retail loyalty through the mediating role of spiritual happiness and the moderating role of store image. Drawing on the Stimulus‑Organism‑Response framework, the study introduces transcendental loyalty as a novel construct that extends beyond cognitive satisfaction to encompass emotional and spiritual fulfillment. A quantitative explanatory design was employed, using a cross-sectional survey of 292 Muslim consumers in selected East Java cities in and around the Tapal Kuda retail corridor, with responses collected both online and offline to ensure contextual relevance. The findings indicate that spiritual happiness helps translate functional stimuli into enduring consumer–brand relationships, while store image is associated with a stronger pathway by validating consumer beliefs and reinforcing trust. Theoretically, this study advances Islamic marketing and sharia economic law by embedding transcendental constructs into loyalty models and linking halal retail behavior with fiqh muamalah and maqashid al-shariah concerns. Practically, it provides guidance for halal retailers to design strategies that integrate Shariah-compliant values, authentic brand positioning, and phygital store image management. These insights contribute to a deeper understanding of how halal retail may sustain long-term loyalty through the alignment of commercial practices with spiritual well-being.